Relationship between Blood Pressure, Blood Glucose and Body Mass Index and Coexisting Prehypertension and Prediabetes among Rural Adults in Niger Delta Region, Nigeria - A. Nwafor; F. C. Mmom; O. Obia; C. Obiandu; V. O. Hart; B. C. Chinko (Highlights on Medicine and Medical Research Vol. 1, 2021)
The incidence of hypertension, diabetes and overweight-obese are emerging health problems, which are increasingly prevalent globally. The objective of the study was to evaluate the prevalence and the relationship between blood pressure, blood glucose and body mass index, and the tendency of developing prehypertension and pre-diabetes in rural adults in the Niger Delta region. A cross-sectional, population-based descriptive design was used. A total sample of 250 subjects aged 20 years and older, that had resided continually in the order of 10 years and above, in the oil and gas extraction environments, were recruited. While body mass index was calculated using internationally accepted standard methods, blood pressure and fasting blood glucose level were recorded also by standard methods, classified and correlated. One-way ANOVA and Pearson’s correlation analyses were used for comparisons between groups. Result showed that although blood pressure and blood glucose measurements increase with age, males had higher prevalence of high blood pressure and raised blood glucose compared with females (p<0.05). Both sexes had almost similar distribution of high body mass index which was not statistically significantly different (p>0.05). In total, overweight coexisted among 14% of participants with normal blood glucose, 19.6% pre-diabetes, 7.6% diabetes, 24% normotensive, 15.4% pre-hypertensive and 1.8% hypertensive. Pre-diabetes coexisted among 9.8% normotensive and pre-hypertensive respectively, while 0.2% normotensive, 5.6% pre-hypertensive, and 18.2% hypertensive had combined diabetes. About 16.4% had both combined diabetes and obesity, and hypertension and obesity. Overall, 19.5% had combined hypertension, obesity and diabetes. In total, the prevalence of obesity was 16.4%, hypertension 18.2% and diabetes 24.0%. The prevalence of coexisting prehypertension and pre-diabetes, pre-non-communicable and main non-communicable diseases was 17.5%, 21.3% and 23.7% respectively. Data analysis revealed positive and linear correlation and statistically significantly different (p<0.001) in the varying degree of complex association of blood pressure and blood glucose as well as body mass index. In conclusion, notwithstanding, this study provides baseline population based data establishing that the populations in the oil bearing communities are at high risk of developing hypertension, diabetes, and overweight-obese together with high prevalence of combination of pre-hypertension and pre-diabetes. The coexisting of significantly high prevalence of prehypertension and pre-diabetes with raised body mass index, in particular, have a more adverse effect by progression to full hypertension and diabetes. There is the need for national programme for prevention, control or delay the burden of the risk factors for non-communicable diseases for oil and gas bearing communities.